Disease Activity May Not Affect the Prognosis of Coexisting Thyroid Cancer in Acromegalic Patients - Gul, Nurdan; Soyluk, Ozlem; Dogansen, Sema Ciftci; Kurtulmus, Neslihan; Yarman, Sema (Experimental and Clinical Endocrinology & Diabetes, 2019)
Acromegaly is known to be associated with high incidence of malignancies probably due to the mitogenic effects of IGF-1. Differentiated thyroid cancer (DTC) is reported to be one of the most frequent malignancies associated with acromegaly. But there is no data about the clinical course of DTC in acromegalic patients. In this study, we evaluated the course of DTC in 14 acromegalic patients retrospectively. Fourteen papillary thyroid cancer patients without acromegaly, who were matched with the acromegalic patient group for age, gender and properties of thyroid cancer, were investigated as the control group. We identified no change in the course and treatment responses of DTC in association with the acromegaly activity, gender, age and disease duration, and all patients were found to be in remission for DTC at the time of investigation. Retrospective analysis of this cohort suggests that the activity of acromegaly may not affect the treatment responses and prognosis of coexisting DTC.
Keywords: acromegaly; differentiated thyroid cancer; activity of acromegaly; prognosis of thyroid cancer